Sparta Life 1967 Winter - San Jose State College:::Creator::::::::::::; Ames, Steven E.:::Editor::::::::::::
Volume 2, number 1. Sparta Life is an instructional laboratory publication published during the academic year by the San Jose State College students under the supervision of the Department of Journalism and Advertising. Our collection contains issues from Winter 1966-Spring 1969, with 9 different issues in all. Sparta Life proclaimed itself to be a combination of fellow SJSU publication "Lyke" and the campus yearbook, "La Torre." It published a variety of articles relating to the university and the college experience in a magazine format. The Winter 1968 issue of the magazine features Harry Edwards: "We Get What's Ours Or We Burn It Down," an article on part-time sociology teacher Harry Edwards who, at the beginning of the fall semester of 1968, had assailed San Jose State College's community for racism and discrimination in housing, athletics, fraternities, sororities, as well as during the admisssion process.